ELECTROMAGNETIC SHIELDING OF CABLES AND MATERIAL USED - Uzokov Islombek (Web of Journals Publishing, 2024)
This work focuses on shielding buried high-voltage (HV) cables, examining two possible screen topologies (open and closed) and various materials (conductive and ferromagnetic). In a closed Shield, the shield surrounds the cables.
Keywords: electromagnetic shielding, electrostatic shielding, magnetostatic, high frequency.